Simbolisasi Wanita dalam Kakawin Arjuna Wiwaha - Yunitha Asri Diantary; I Made Hartaka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Women have an important position and role in life, not only appearing as sacred beings who are adored. Women are also chased and coveted by the opposite sex to become lovers and wives. Women are often the center of attention because of their beauty and beauty. In kakawin arjuna wiwaha women have a very central position in achieving the mission of saving the three worlds. In accordance with the civilization of the gods, women are not only equal to men, but men are also very dependent on women. The Gods will not be able to carry out their duties perfectly whether in creating, maintaining or fusing without a partner as a source of strength. So that the gods Brahma, Visnu, and Siva can only carry out their main tasks and functions when there is magic. Likewise with men in life in the world they will not be able to carry out their swadharma properly without encouragement or motivation from their women. The influence of women is so great in this life, that society should be able to glorify women and appreciate them more. Women in the kakawin arjuna wiwaha have several positions that depict special symbols or signs according to their roles, such as testing the firmness of a man's faith, women as goddesses, women as weapons and women as wives.